Evaluation of Cardiac Autonomic Function Testing In a Tertiary Care Hospital - Arun Kumar Moha; Thejaswini K O; Mahantha M; Srinivas P; Sumali Sharma; Vivek Veeraiah, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Introduction: The autonomic function testing (AFT) refers to the evaluation of the sympathetic, and parasympathetic division of autonomic nervous systems (ANS). The system affects function of almost every organ system in the body; hence, many tests that seem unique to a particular organ are really tests of autonomic function (e.g., urodynamic studies, gastric motility testing, pupillometry, tests of salivary and lacrimal gland secretion, etc.). Through scientific research and clinical experience published in peer-reviewed journals, autonomic function testing has proven its worth in the diagnosis and treatment of autonomic disorders over the past many years. Autonomic testing is now considered as a crucial part of the clinical assessment. Materials and methods: The present work was designed and conducted in the Department of Physiology at Sri Siddhartha Institute of Medical Sciences & Research Centre (T Begur), Sri Siddharatha Academy of Higher Education., Tumkur over a period of 12 months. Fifty healthy male subjects doing MBBS in the same college between 19-24 years volunteered to participate in the present study. On the basis of detailed family history, participants were divided into two groups of twenty-five each as study group- with family history of hypertension (FH+) and control group- without any family history of hypertension (FH-). Either or both parents of the subjects of study group presented with history of hypertension of varying degree and duration and were under antihypertensive therapy which was further confirmed by their medical prescriptions as well. Both the groups were assessed and compared for their autonomic function tests to find out hyper-reactors for those having higher risk for hypertension in future. Sample size of 50 participants was decided including both the groups due to lack of consent from most of the senior MBBS students. Results: There were no significant differences between age, BMI and other physical indices between two groups. All the physical characteristics of subjects of control as well as study group were statistically matched (p >0.05). However, the resting heart rate, systolic and diastolic blood pressures were found to be marginally higher (p>0.05) in the study group (Table 1). There was higher and significant (p <0.001) rise in diastolic blood pressure following isometric hand grip test at 1/3 of MVC and cold pressor tests in study group as compared with the control group indicating an attenuated sympatho-adrenergic system in subjects of study group (Table 2). Conclusion: It may be concluded that sympathetic nervous system hyperactivity develops in children of hypertensive parents whereas the PNS remains unaltered. Though the subjects of study group may be normotensive initially, there is possibility of development of hypertension in future. Hyper-reactors who have positive family history were more vulnerable to future hypertension due to their sympathetic over activity. Regular monitoring of autonomic activity may prove to be a useful tool in predicting the future hypertensive cases. It also appears that genetic and environmental factors might be responsible for essential hypertension in families.